Peranan Bank Indonesia Sebagai Pengawas Dalam Penyelesaian Kredit Macet Di Indonesia - Muhammad Zaky (Universitas Budi Luhur, 2017)
The central bank of Indonesia has the authorities as a regulator and oversees the commercial banks in Indonesia. One of the authorities of Bank Indonesia is to minimize the risks from the banking world which in turn can protect the people who deposit their funds in banks. One of the most vulnerable banking risks is the problem of bad debts. The problem of bad debts psychologically it can cause concern both from the side of bankers and from debtors. Banks should be careful in giving credit, while for the debtors may be reluctant to apply for credit to the bank because the worry is considered stuck. In this study will examine the subject matter through the normative-empirical approach (socio legal) ie research of legislation (legal studies), which uses empirical studies with social science methodological approach. Normative approach is done to analyze the legal system related to bad credit. While the empirical approach is done to determine the causes of bad loans from the perspective of people who receive credit, and how the regulations have been implemented to deal with bad debts. Empirical research is done by using several sources of information.